PENATALAKSANAAN FISIOTERAPI PADA OSTEOARTHTRITIS KNEE BILLATERAL DENGAN MODALITAS TENS , LASER DAN TERAPI LATIHAN DI RSUD BENDAN KOTA PEKALONGAN - Dimas Adi Anggoro; Irine Dwitasari Wulandari (LPPM Universitas Pekalongan, 2019)
Background: Osteoarthritis is a chronic joint disorder accompanied by bone and joint damage, in the form of progressive disintegration and softening followed by increased growth of the bone edge and cartilage of the knee joint (osteophytes) and fibrosis in the capsule of the knee joint. spasm, limited scope of joint motion, muscle weakness and decreased functional activity. Examination of physiotherapy includes examination of pain with the Visual Analogue Scale, spasm with palpation, the scope of motion of the joint with the goneometer, muscle weakness with Manual Muscle Testing, and functional activity with the Womac index. Objective: To determine the effect of Physiotherapy Management on the conditions of Osteoarthritis of the Knee Billateral with the modalities of TENS, LASER and Exercise Therapy. Method: This study was conducted at Bendan Pekalongan Hospital with a descriptive analytic research design. The research subjects in this scientific paper are patients with billateral osteoarthritisitis with the modalities of TENS, LASER and Exercise Therapy. The method of data collection is the data analysis of this study using the autoanamnesis method, the research instrument is pain examination, spasm, joint motion range, muscle strength and functional activity Results: Based on the therapy carried out 5 times the following results were obtained: (1) there was a decrease in pain from T1 = 4 to T5 = 2 (2) there was a decrease in spasm from T1 = 1 to T5 = 0 (3) there was an increase in knee flexion ROM from T1 = 100 ° to T5 = 120 ° (4) there is an increase in muscle strength from T1 = 4 to T5 = 5 (5) there is an increase in daily functional activities. Conclusion: Physiotherapy interventions with modalities of TENS, LASER and Exercise Therapy can reduce problems that arise in the condition of the Knee Billateral Osteoarthritis.